Upaya peningkatan kesadaran preventif terhadap diabetes mellitus pada generasi milenial - Riana Sari Puspita Rasyid; Susilawati; Arwan Bin Laeto; Rara Inggarsih; Masayu Farah Diba (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2020)
Efforts to increase preventive awareness of non-communicable diseases in millenials. Diabetes mellitus is a non-communicable disease that causes metabolic disorders. The etiology of diabetes mellitus is including heredity, viruses that cause pancreatic beta cell damage, diet, obesity, activity patterns, environment and sleep habits. Community service activities aim to increase adolescent knowledge of the prevention of non- communicable diseases, especially diabetes mellitus. Activities carried out in the form of counseling about the signs and symptoms of general symptoms and risk factors for non-communicable diseases and its complications, independent analysis of sleep quality, body mass index), measurement of upper arm circumference and analysis of blood glucose levels. The results of this activity obtained an increase in adolescent insight about non-communicable diseases (especially diabetes mellitus) and increase knowledge about promotive and preventive from this diseases. Continuous service activities are needed to be carried out to the adolescents so that public health can improve.